The Effect Of Human Resource Quality, Use Of Information Technology And Internal Control System On The Value Of Skpd Financial Reporting Information In The Government Of Barito Kuala District - Anggara Pratama; Melania, Melania; Sylvia Yuanita Banjuradja (Jurnal Multidisiplin Sahombu, 2023)
This study aims to analyze the Quality of Human Resources (X1), the Utilization of Information Technology (X2), and the Internal Control System (X3) on the Financial Reporting Information Value of Local Government Agencies (SKPD) in Barito Kuala Regency (Y) both simultaneously, partially, and dominantly. The research was conducted in July 2023, employing a quantitative data analysis method using a questionnaire as the research instrument distributed to 47 SKPD, with each SKPD represented by one respondent. The data analysis method utilized multiple linear regression analysis with the SPSS program. The research findings revealed an Adjusted R Square value of 0.656, indicating a strong correlation between X1, X1, X2, and X3 significantly influence Y simultaneously. According to the t-test, only X3 had a significant partial impact on Y. Furthermore, X3 had the highest standardized coefficient beta, establishing its dominant influence.